2004
DOI: 10.1103/physreva.69.053818
|View full text |Cite
|
Sign up to set email alerts
|

Atomic four-levelNsystems

Abstract: We investigate the atomic four-level N configuration both analytically and numerically, for various pump and probe intensities, with and without transfer of coherence (TOC) and Doppler broadening, and compare the results obtained to those of realistic atomic systems. We find that TOC affects the whole spectrum, in addition to producing an electromagnetically induced absorption (EIA) peak at line center. We show that the EIA peak splits as the pump intensity increases. These results are compared with those of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 24 publications
8
100
0
1
Order By: Relevance
“…This is because the Jaynes-Cummings coupling between the two-level system and the mechanical resonator can lead to dressed states, which have a more complicated energy structure. This usually leads to a more complicated absorption of a weak probe field by a hybrid system, and can be referred to as an EIT in a multi-level atom system [88][89][90].…”
Section: Electromagnetically-induced Transparencymentioning
confidence: 99%
“…This is because the Jaynes-Cummings coupling between the two-level system and the mechanical resonator can lead to dressed states, which have a more complicated energy structure. This usually leads to a more complicated absorption of a weak probe field by a hybrid system, and can be referred to as an EIT in a multi-level atom system [88][89][90].…”
Section: Electromagnetically-induced Transparencymentioning
confidence: 99%
“…The reason for the above result can be qualitatively explained as follows. Our atomic system is a kind of atomic configuration which owns the property of the double-dark resonances [21,22]. Under this condition, the coherent interaction for this atomic system can lead to the emergence of sharp spectral features of interacting double-dark resonances which strongly modify the optical properties of the double EIT windows.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Using an N -configuration atom, Taichenachev et al [12] have shown that the sign of the absorption resonance can change, depending on the rate of coherence transfer, and that EIA can turn into enhanced transmission in the case of zero or even a low rate of coherence transfer. EIA in an N -type interaction scheme has also been investigated for various pump and probe intensities with and without transfer of coherence and Doppler broadening in [13], both analytically and numerically. The results were compared with the results obtained for realistic atomic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [12], the role of the ground-state Zeeman coherence, transfer to the excited-state coherence was not discussed. In [13], it was shown that the transfer of coherences can affect the whole spectrum, not only the EIA peak. The spontaneous transfer of Zeeman coherences from the excited to ground levels influences, as shown in [11], the nonlinear resonances in probe-field spectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation